The Correlation between Attitude Toward Using (ATU) and Behavioral Intention (BI) in Students Using Scola Biology Teaching at Dedikasi Edukasi Kualiva Senior High School - Miftahul Jannah; Relsas Yogica; Heffi Alberida; Helsa Rahmatika; Moralita Chatri (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Broad and complex biology topics require electronic learning media such as Scola to assist students in learning. Student responses are important to know in the use of IT systems as an evaluation. The aim of this study was to find out the value of ATU and BI values in the use of Scola, the correlation between ATU and BI in students using Scola in biology learning at DEK High School. The type of this study was descriptive correlation with a quantitative approach conducted at DEK SMA. The sample of this research consisted of 48 students using the total sampling technique. The data analysis used was the Pearson Product Moment correlation test and the t test and it was found that the data were normally distributed. The results showed that Attitude Toward Using was 72% with high criteria. Behavioral Intention was 74% with high criteria, and the correlation between ATU and BI had a value of r = 0.74 (strong correlation) this means that there is a positive correlation and the t test results obtained tcount = 7.37 which is greater than ttable = 1.67. Dealing with the results of the study, it can be concluded that ATU has a significant positive correlation to BI in students who use Scola in biology learning at DEK Senior High School.